Sulphonamide inhibition studies of the beta-carbonic anhydrase GsaCA beta present in the salmon platyhelminth parasite Gyrodactylus salaris - Aspatwar Ashok; Bonardi Alessandro; Aisala Heidi; Zueva Ksenia; Primmer Craig R; Lumme Jaakko; Parkkila Seppo; Supuran Claudiu T (TAYLOR & FRANCIS LTD, 2025)
A beta-class carbonic anhydrase (CA, EC 4.2.1.1) present in the genome of the Monogenean platyhelminth Gyrodactylus salaris, a fish parasite, GsaCA beta, has been investigated for its inhibitory effects with a panel of sulphonamides and sulfamates, some of which in clinical use. Several effective GsaCA beta inhibitors were identified, belonging to simple heterocyclic sulphonamides, the deacetylated precursors of acetazolamide and methazolamide (K (I)sof 81.9-139.7 nM). Many other simple benezene sulphonamides and clinically used agents, such as acetazolamide, methazolamide, ethoxzolamide, dorzolamide, benzolamide, sulthiame and hydrochlorothiazide showed inhibition constants <1 mu M. The least effective GsaCA beta inhibitors were 4,6-disubstituted-1,3-benzene disulfonamides, with K (I)s in the range of 16.9-24.8 mu M. Although no potent GsaCA beta-selective inhibitors were detected so far, this preliminary investigation may be helpful for better understanding the inhibition profile of this parasite enzyme and for the potential development of more effective and eventually parasite-selective inhibitors.